Identification of Bioactive Compound Function Groups in Mangosteen Fruit Peel Extract (Garcinia mangostana L.) and Lime Extract (Citrus aurantifolia Swingle) as Anticholesterol Agents Using Fourier Transform Infrared (FTIR) - Ananda Nur Faizah; Sagita Aulia Putri; Irul Hidayat; Eva Agustina; Nova Lusiana; Risa Purnamasari; Funsu Andiarna (International Conference on Sustainable Health Promotion, 2025)
Hypercholesterolemia is one of the major risk factors for cardiovascular diseases such as atherosclerosis and coronary heart disease. The main commonly used therapy is synthetic drugs such as statins, but long-term consumption is known to cause side effects such as liver damage, muscle disorders, and metabolic disorders. Therefore, the search for safer natural alternatives is important. Mangosteen rind (Garcinia mangostana L.) and lime peel (Citrus aurantifolia Swingle) are known to contain bioactive compounds such as xanthones, flavonoids, and phenolic acids that have potential as anticholesterol agents. This study aims to identify the functional groups of bioactive compounds in mangosteen and lime peel extracts using Fourier Transform Infrared (FTIR) and compare their potential as anticholesterol candidates. The extracts were obtained through maceration method using 70% and 96% ethanol solvents. FTIR analysis showed the presence of O-H (phenol), C=O (carbonyl), and C-O (ester) functional groups, indicating the presence of active compounds such as α-mangostin in mangosteen peel and flavonoids such as quercetin in lime peel. The peak absorption intensity of O-H and C=O groups in mangosteen peel extract is higher than that in lime peel extract. These results indicate that mangosteen peel extract contains a higher concentration of bioactive compounds, so it has the potential to provide an anticholesterol effect.